2016
DOI: 10.1016/j.math.2015.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed body perception, reduced sleep, and kinesiophobia in subjects with pregnancy-related persistent lumbopelvic pain and moderate levels of disability: An exploratory study

Abstract: Disturbances in body-perception, sleep and elevated kinesiophobia were found in pregnancy-related lumbopelvic pain subjects with moderate disability, factors previously linked to persistent low back pain. The cross-sectional nature of this study does not allow for identification of directional pathways between factors. The results support the consideration of these factors in the assessment and management of pregnancy-related lumbopelvic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
51
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 69 publications
9
51
3
Order By: Relevance
“…There are contradictory reports about this matter in literature. Some studies are consistent with the results of the present study whereas some are not . The increase of sacroiliac dysfunction during the course of pregnancy, as found in the present study, is an important finding because there is a relation between increasing pain intensity and reduced mobility affecting the daily activities of pregnant women with sacroiliac dysfunction.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…There are contradictory reports about this matter in literature. Some studies are consistent with the results of the present study whereas some are not . The increase of sacroiliac dysfunction during the course of pregnancy, as found in the present study, is an important finding because there is a relation between increasing pain intensity and reduced mobility affecting the daily activities of pregnant women with sacroiliac dysfunction.…”
Section: Discussionsupporting
confidence: 91%
“…It has been reported that 25% of pregnant women with sacroiliac dysfunction have serious pain and 8% experience severe disability during and after the pregnancy . Also, pregnant women with sacroiliac dysfunction will experience sacroiliac dysfunction again during a subsequent pregnancy . Severe pain (a score of more than 7/10 on a visual analog scale) in the first trimester is a major predictor of chronic pain; therefore, early intervention, effective pain relief, and reassurance are crucial .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the score on the FreBAQ questionnaire in the CP_Pain population was no different from that seen in a matched group with LBP and no CP and very similar to the results of previous investigations that have used the FreBAQ to assess body perception in general LBP populations . This builds on work demonstrating that lumbopelvic self‐perception is impaired in people with LBP compared to matched control groups and extends this finding to include people with LBP and CP.…”
Section: Discussionsupporting
confidence: 84%
“…Neuroimaging studies of people with chronic low back pain (CLBP) suggest structural and functional changes in cortical areas that are thought to subserve body perception . Several studies have reported that people with CLBP feel a sense of alienation and rejection of the back, represent the back differently when asked to draw how the back feels to them, and endorse questionnaire items associated with altered perceptual awareness of the back . Furthermore, psychophysical findings consistent with disruption of the mechanisms that underpin body image, such as decreased lumbar tactile acuity, problems localizing sensory input, poor graphesthesia performance, spatially defined tactile processing deficits, greater lumbar repositioning error, decreased lumbar motor precision, poor trunk motor imagery performance and impaired visual recognition of actions specific to the back also appear to be features of CLBP.…”
Section: Introductionmentioning
confidence: 99%